Double-Balloon Endoscopy in Overt and Occult Small Bowel Bleeding: Results, Complications, and Correlation with Prior Videocapsule Endoscopy in a Tertiary Referral Center - Carlijn Hermans; Arnold Stronkhorst; Annemarie Tjhie-Wensing; Jan Kamphuis; Bas van Balkom; Rob Dahlmans; Lennard Gilissen (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims Videocapsule endoscopy (VCE) and double-balloon endoscopy (DBE) allow deep exploration in patients with suspected small bowel pathology. VCE is often performed as an initial small bowel examination to explore whether an intervention by DBE is indicated and to determine insertion route. The study aim was to evaluate the correlation between DBE and VCE in patients with obscure or overt bleeding or anemia, as well as intervention frequency, and complications. Methods Retrospective observational study. Results DBE procedures (n=205) showed small bowel lesions in 64% cases. Antegrade DBE showed positive results in 79% cases, mostly angiodysplasias (63%). Retrograde DBE showed positive results in 22% cases. An intervention was performed in 64% of DBE procedures. The major complication rate was 0.5%, which was one case of perforation. Pancreatitis did not occur. The overall diagnostic agreement was 66% among the 134 DBEs with preceded VCE. Conclusions In cases of overt or occult bleeding or anemia, DBE was positive in 64%, with only a few complications. Positive correlation was 66% among initially performed VCEs and DBEs. Owing to the time-consuming and invasive character of DBE, performing VCE before DBE might still be clinically relevant.